2001
DOI: 10.1021/jm011025r
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Benzothiazoles. 16. Synthesis and Pharmaceutical Properties of Antitumor 2-(4-Aminophenyl)benzothiazole Amino Acid Prodrugs

Abstract: A series of water-soluble L-lysyl- and L-alanyl-amide prodrugs of the lipophilic antitumor 2-(4-aminophenyl)benzothiazoles has been synthesized to address formulation and bioavailability issues related to the desired parenteral administration of the chosen clinical candidate. The prodrugs exhibit the required pharmaceutical properties of good water solubility (in weak acid) and stability at ambient temperature and degradation to free base in vivo. The lysyl-amide of 2-(4-amino-3-methylphenyl)-5-fluorobenzothia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
208
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(211 citation statements)
references
References 13 publications
(25 reference statements)
0
208
0
3
Order By: Relevance
“…This discovery was followed by the identification of the 2-(4-amino-3-methylphenyl)benzothiazole (DF 203, NSC 674495) and 2-(4-amino-3-methylphenyl)-5-fluorobenzothiazole (5F 203, NSC 703786) and the evaluation of the analogue compounds with more potent and diverse activities [8][9][10][11][12][13][14] . Phortress (NSC 710305, dihydrochloride salt of the lysylamide prodrug of 2-(4-amino-3-methylphenyl)-5-fluorobenzothiazole (5F 203)), the fluorinated water-soluble pro-drug, which has been synthesized to address formulation and bioavailability issues related to the desired parenteral administration [15][16][17][18][19] , was then chosen for phase 1 The mechanism of action involves formation of reactive intermediates that can bind covalently to DNA and can be metabolized only by sensitive cancer cell lines 21 . Conversely, in insensitive cell lines, neither retaining nor metabolization occurs, thereby selective antitumor properties appear due through to metabolism [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…This discovery was followed by the identification of the 2-(4-amino-3-methylphenyl)benzothiazole (DF 203, NSC 674495) and 2-(4-amino-3-methylphenyl)-5-fluorobenzothiazole (5F 203, NSC 703786) and the evaluation of the analogue compounds with more potent and diverse activities [8][9][10][11][12][13][14] . Phortress (NSC 710305, dihydrochloride salt of the lysylamide prodrug of 2-(4-amino-3-methylphenyl)-5-fluorobenzothiazole (5F 203)), the fluorinated water-soluble pro-drug, which has been synthesized to address formulation and bioavailability issues related to the desired parenteral administration [15][16][17][18][19] , was then chosen for phase 1 The mechanism of action involves formation of reactive intermediates that can bind covalently to DNA and can be metabolized only by sensitive cancer cell lines 21 . Conversely, in insensitive cell lines, neither retaining nor metabolization occurs, thereby selective antitumor properties appear due through to metabolism [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…5 The compounds possess benzothiazole nucleus in their structure are involved in research aimed at evaluating new chemotherapeutically active agents: such as antimicrobial [6][7][8][9] a topical carbonic anhydrase inhibitor, 10 a cyclooxygenase inhibitor, 11 antitubercular, 12,13 antinematode, 14 a dual inhibitor of thromboxane A 2 synthetase and 5-lipoxygenase 15 , a selective and reversible inhibitor of monoamine oxidase type A (MAO-A), 16 antiallergic, 17 multi-drug resistance cancer cell activities with inhibiting activity on eukaryotic topoisomerase II enzyme in cell-free system [18][19][20] and antitumor agents. [21][22][23] Currently, a new series of benzothiazoles have been synthesized as antitumor agents and showed potent inhibitory activity against human breast cancer cell lines in vitro and in vivo. 21 Among them, lysyl-amide of 2-(4-amino-3-methylphenyl)-5-fluorobenzothiazole (Formula 1) had been selected for phase 1 clinical evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…21 Among them, lysyl-amide of 2-(4-amino-3-methylphenyl)-5-fluorobenzothiazole (Formula 1) had been selected for phase 1 clinical evaluation. 22 In the last years, we reported the synthesis of several 2-substitutedbenzothiazole derivatives as the anti- microbial agents 7,8 as seen in Formula 2. According to these studies the compounds were found to have inhibitory effect with MIC value of 3.12-50 µg/ml against some of Gram-positive, Gram-negative bacteria and Candida albicans as yeast.…”
Section: Introductionmentioning
confidence: 99%
“…The benzothiazole skeleton constitutes an important template for a wide variety of biologically active compounds. This molecule and its derivatives are known to be powerful antitumour agents [2,3], calmodulin antagonists [4], neurotransmission blocker [5], and neuroprotective agent [6]. Benzothiazole type compounds attracted considerable attention in anticancer drug development [7,8].…”
Section: Introductionmentioning
confidence: 99%